Artificial Intelligence and Machine Learning in Genomic Medicine: Redefining the Future of Precision Diagnostics - Sambasiva Rao Suura (South Eastern European Journal of Public Health, 2025)
The integration of Artificial Intelligence (AI) and Machine Learning (ML) into genomic medicine is revolutionizing the landscape of precision diagnostics, offering unprecedented opportunities to personalize healthcare and enhance clinical decision-making. Advances in next-generation sequencing (NGS) technologies have generated vast amounts of genomic data, creating both challenges and opportunities for clinicians and researchers. AI and ML algorithms, such as deep learning, support vector machines, and random forests, are being leveraged to analyze complex genomic data, identify genetic markers, and predict disease risk with remarkable accuracy. These tools enable the identification of subtle patterns in genetic variations, providing insights into the molecular mechanisms underlying diseases and facilitating the development of individualized treatment strategies. Furthermore, the ability of AI to process multi-omics data (e.g., genomic, transcriptomic, proteomic) enhances the precision and comprehensiveness of diagnostic predictions. However, the adoption of these technologies faces hurdles such as data privacy concerns, ethical considerations, and the need for robust validation in clinical settings. As AI and ML continue to evolve, they hold the potential to redefine the future of precision diagnostics, enabling earlier detection, improved treatment outcomes, and more efficient healthcare systems. This paper explores the current state of AI and ML in genomic medicine, its applications, challenges, and the transformative role it will play in shaping the future of personalized healthcare.